(untitled) (Journal of Economic Research & Business Administration, 2018)
This paper proposes new directions in researching innovation in small and medium sized enterprises (SMEs) based on a process perspective. This article includes key factors of innovative development of SME, which are restricted it. Moreover, it is described the structure of SME financing in the Republic of Kazakhstan, defined the main problems of financing SME and made conclusion about using international experience in this way. We propose that our current level of understanding is restricted due to the theoretical and methodological biases that have informed existing research. A better understanding is more likely to be achieved by rejecting normative-variance approaches and assessing innovation in the context of strategic conduct within institutional processes and structures. This should contribute to a better appreciation of innovation in SMEs by focusing on the process of change.